Promoting Self-Regulatory Management of Chronic Pain Through Dohsa-hou: Single-Case Series of Low-Functioning Hemodialysis Patients - Haramaki, Yutaka; Kabir, Russell Sarwar; Abe, Kazuaki; Yoshitake, Takashi (Frontiers in Psychology, 2019)
Hemodialysis patients suffer from long-term pain that drains their energy and contributes to behavioral interference and other negative effects on their daily lives that result in or exacerbate functional limitations. In addition, they deal with dietary restrictions, symptoms such as itching, lack of energy, and psychological stressors like the loss of self-concept and self-esteem. Self-regulation involves the capacity to notice, inform, and modulate responses and behavior, and research indicates that it promotes rehabilitation in chronic pain patients. Research on the aspects of self-regulation afforded by the Japanese psychotherapy Dohsa-hou correspond to psychological processes tied to the sense of self-control that clients realize over their body movements. This study pilot tested a hospital-integrated implementation of Dohsa-hou relaxation tasks as a chronic pain management behavioral intervention for five female hemodialysis patients between the ages of 59–62 years. We conducted an ABABABA single-case design to compare baseline A-phases (treatment-as-usual: TAU) taken at recurring one-week intervals (3 sessions per week for a total of 4 weeks, 12 total recordings) with an intervention of Dohsa-hou B-phases every 4 weeks (3 sessions per week for 12 weeks, 36 total recordings) over the span of 4 months to compare effectiveness. Visual Analogue Scale (VAS) pain scores between phases were taken and self-regulatory progress was tracked and summarized from a series of semi-structured interviews. Visual analysis of scores for each participant as single cases indicated decreases for the Dohsa-hou phase compared to baseline treatment-as-usual. As a result, participants reported using Dohsa-hou to reduce pain and experienced improvements in quality of life associated with greater self-regulatory capacity to attend to personal care and domestic activities. These preliminary findings suggest that Dohsa-hou body movement relaxation tasks were feasible as a coping skill in a hospital-integrated setting and at home and show promise for promoting quality of life vis-a-vis the management of severe and chronic bodily pain associated with end-stage renal disease and its treatment, particularly by improving aspects of pain-mediated self-regulatory fatigue.